Strategically On The Maritime Silk Route Maritime Treasures Off The Malay Peninsula - Ooi, Keat Gin (2014)
The Malay Peninsula or what is present day WestlPeninsular Malaysia is flanked on either shores by the South China Sea on the east and the Straits of Malacca (Melaka) on the west, both essentially important sea-borne passages between the East and the West. By the first millennium BCE and the early part of the first millennium CE the Malay Peninsula possessed coastal trading sites and on the lower reaches of rivers. Complementing the peninsula's strategic location was the seasonal monsoonal pattern that facilitated the comings and goings of merchants enabling long-distant maritime trade to flourish. The peninsula acted as a 'connector' for the confluence of traders from East Asia to interact with counterparts from South and West Asia as well as from Southeast Asia.